The impact of Sukuk on the country’s economic growth with country governance as a moderating variable - Irma Yuliani; Ibnu Qizam; Arif Nugroho; Zul Ihsan Mu'arrif (al-Uqud : Journal of Islamic Economics, 2022)
This study examines the impact of Sukuk on economic growth with country governance (regulatory quality, the rule of law, and government effectiveness) as the moderating variable. Five countries, Indonesia, Malaysia, United Arab Emirates, Bahrain, and Saudi Arabia were taken as samples. Data taken were from 2006 to 2018. Moderating Regression Analysis (MRA) was used to test the effect of the variables in the country's governance in moderating the relationship between Sukuk and economic growth. The Generalized Least Square (GLS) was used to minimize the variance in the estimation model. The findings of this study indicate that the Sukuk development moderated by the regulatory quality has a significant positive effect on the country's economic growth. At the same time, the other two moderating variables (the rule of law and government effectiveness) did not show a significant moderation effect. The regulatory quality shows the policy's efficiency implemented by the government and Sukuk innovation.